Heating Transfer Investigation of Heater in Heat Supply System of Field Hospital Operating in Emergency - I. L. Kachar (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Criteria dependences for assessment of heat transfer value under conditions natural convection (a horizontal slot) have been obtained in the paper. The dependences are applicable for heaters in heat supply systems.